UPAYA MENINGKATKAN DISPOSISI MATEMATIS DAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK MELALUI STRATEGI PEMBELAJARAN INKUIRI JURISPRUDENSIAL - Sylvi Yuliawati (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
The research aim was improve students’ mathematical disposition and critical thinking ability on mathematical learning by using jurisprudential inquiry strategy. The research approach used in this study were qualitative and quantitative approach while the method used was Classroom Action Reseacrh, which conducted three cycles with research design including planning, implementation of action, observation, and reflection. The subject of research was the students of XI MO 4 class, one of vocational high school in sub district Majalaya, Bandung regency. The research instruments were observation sheets, formative tests, questionnaires, and journals. The test was analyzed by counting students’ absorption rate and classical absorption rate. While the questionnaire and observation using percentage. The result of this research shows that the mathematical learning by using Jurisprudential Inquiry Strategy was done well. Students’ mathematical dispositions and critical abilities increased after mathematical learning by using inquiry strategies, as well as positive students’ responses to mathematical learning by using Jurisprudential Inquiry Strategy.